Baby Bear$1 (Bs Christmas s - Ross, Dave, 1949- (New York : W. Morrow, 1985)
Baby Bear$1 (Bs walk on Christmas Eve nearly ends in disaster.s
Keywords: Bears -- Fiction; Winter -- Fiction; Christmas -- Fiction